IBM TotalStorage Productivity Center V2.3 : getting started - Lovelace, Mary; McGimsey, Larry; Gomilsek, Ivo; Marquez, Mary Anne (IBM redbooks., 2005)
IBM TotalStorage Productivity Center is a suite of infrastructure management software that can centralize, automate, and simplify the management of complex and heterogeneous storage environments. It can help reduce the effort of managing complex storage infrastructures, improve storage capacity utilization, and improve administration efficiency. IBM TotalStorage Productivity Center allows you to respond to on demand storage needs and brings together, in a single point, the management of storage devices, fabric, and data. This IBM Redbooks publication is intended for administrators and users who are installing and using IBM TotalStorage Productivity Center. It provides an overview of the product components and functions. We describe the hardware and software environment required, provide a step-by-step installation procedure, and offer customization and usage hints and tips. This book is not a replacement for the existing IBM Redbooks, or product manuals, that detail the implementation and configuration of the individual products that make up the IBM TotalStorage Productivity Center , or the products as they may have been called in previous versions. We refer to those books as appropriate throughout this book.